WORD FORMATION: PRODUCTIVE TYPES - Abduvahobova Sevara Sobirjon qizi (TADQIQOTLAR.UZ, 2024)
Annotation: Word formation is the process of creating new words from existing ones. There are many different ways to form new words, but some of the most productive types include: • Affixation: Adding prefixes or suffixes to words to change their meaning, part of speech, or both. For example, the prefix "un-" can be added to the adjective "happy" to create the adjective "unhappy", or the suffix "-ly" can be added to the adjective "quick" to create the adverb "quickly". • Compounding: Combining two or more words to create a new word. For example, the words "black" and "board" can be combined to create the word "blackboard". • Conversion: Changing the part of speech of a word without changing its form. For example, the noun "love" can be used as a verb, as in "I love you". • Acronyms: Forming a new word from the first letters of a phrase or series of words. For example, the word "laser" is an acronym for "light amplification by stimulated emission of radiation". • Blending: Combining parts of two or more words to create a new word. For example, the word "smog" is a blend of the words "smoke" and "fog".